Hyperkalemia influences the outcome of patients with cirrhosis with acute decompensation (AD) and acute on chronic liver failure (ACLF) - Kumar, Ujjwal; Mishra, Prakash Chandra (Student’s Journal of Health Research Africa, 2024)
Background: Liver cirrhosis is a chronic liver disease which affects multiple organs and is generally associated with electrolyte imbalance which is hyperkalemia. Hyperkalemia with cirrhosis that is associated with acute decompensation and acute-on-chronic liver failure have fatal outcomes. Method: This was a prospective observational study conducted to determine the influence of hyperkalemia on liver cirrhosis. This study was conducted at ‘ABC’ institute for a period of a year. The biochemical screening was performed. Mortality rates were recorded. The obtained data was subjected to statistical analysis to obtain the prediction of mortality with hyperkalemia. Results: 657 patients participated in this study. Amongst them, 147 patients had existing acute or chronic liver failure, whereas 56 of them developed acute or chronic liver failure during their hospital stay for 28 days. 72 patients who were admitted for liver cirrhosis also had hyperkalemia along with it. There were 45 patients who developed hyperkalemia during the course of the study. 128 patients with ACLF died within 90 days of follow-up. The statistical analysis predicted the mortality in the patients after 90 days as well in the patients who had average potassium levels from the admission above 5 mEq/L. Conclusion: Hyperkalemia is associated with an increased mortality rate in patients with cirrhosis in cases of ACLF and AD. 90-day mortality rate increases significantly in patients who have hyperkalemia with ACLF. Recommendation: Hyperkalemia should be used as a prognostic tool to assess the mortality associated with the current disease state and to determine the severity of the case in patients with ACLF.